Dengue virus transovarial transmission by Aedes aegypti - Hartanti, Monica Dwi; Suryani, Suryani; Tirtadjaja, Ingrid A. (Universa Medicina, 2010)
Dengue is a disease that is caused by dengue virus and transmitted to humans through the bite of infected Aedes mosquitoes, especially Aedes aegypti. The disease is hyper-endemic in Southeast Asia, where a more severe form, dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS), is a major public health concern. The purpose of the present study was to find evidence of dengue virus transovarial transmision in local vectors in Jakarta. Fifteen Aedes larvae were collected in 2009 from two areas in Tebet subdistrict in South Jakarta, namely one area with the highest and one with the lowest DHF prevalence. All mosquitoes were reared inside two cages in the laboratory, eight mosquitoes in one cage and seven mosquitoes in another cage and given only sucrose solution as their food. The results showed that 20% of the mosquitoes were positive for dengue virus. Dengue virus detection with an immunohistochemical method demonstrated the occurrence of transovarial transmission in local DHF vectors in Tebet subdistrict. Transovarial dengue infection in Ae.aegypti larvae appeared to maintain or enhance epidemics. Further research is needed to investigate the relation of dengue virus transovarial transmission with DHF endemicity in Jakarta.